2014
DOI: 10.1071/ah13085
|View full text |Cite
|
Sign up to set email alerts
|

Expanding emergency department capacity: a multisite study

Abstract: Objectives. The aims of the present study were to identify predictors of admission and describe outcomes for patients who arrived via ambulance to three Australian public emergency departments (EDs), before and after the opening of 41 additional ED beds within the area.Methods. The present study was a retrospective comparative cohort study using deterministically linked health data collected between 3 September 2006 and 2 September 2008. Data included ambulance offload delay, time to see doctor, ED length of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…As our research indicates, handover can be a time when communication breakdown occurs and patients are left with minimal care and/or needing to repeat their story. Whilst research has indicated that professional's expectations and experiences often are likely to influence quality of handover, results have also indicated that communication, in particular a lack of active listening, has been an issue in handovers . In a qualitative study analysing patients' experiences of handover, communication and bedside manner were also found to impact on patient satisfaction levels during the handover experience, and that patients desired improved communication during their hospital handovers .…”
Section: Discussionmentioning
confidence: 98%
“…As our research indicates, handover can be a time when communication breakdown occurs and patients are left with minimal care and/or needing to repeat their story. Whilst research has indicated that professional's expectations and experiences often are likely to influence quality of handover, results have also indicated that communication, in particular a lack of active listening, has been an issue in handovers . In a qualitative study analysing patients' experiences of handover, communication and bedside manner were also found to impact on patient satisfaction levels during the handover experience, and that patients desired improved communication during their hospital handovers .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the third study looked at the effects of expanding ED bed capacity from 81 beds to 122 beds, across three Australian hospitals 23. Over a 2-year period, the authors reported only one outcome to improve: in-hospital mortality.…”
Section: Potential Solutions To Exit Blockmentioning
confidence: 99%
“…Crilly et al, 2014). In terms of hospitalisation, these findings indicate that the nursing care needs of hospitalised patients were higher in comparing to those of the home-discharged patients.…”
mentioning
confidence: 77%
“…In addition, the patient age was an important predictor of nursing time in different settings; the older the patient was, the more time nurses spent with direct care of patients (McGillis Hall, Doran, & Pink, ; O'Brien Pallas, Irvine, Peereboom, & Murray, ). Higher age in ED patients, besides its correlation with JDT, was associated with longer ED‐LOS (Kreindler, Cui, Metge, & Raynard, ) and both age and ED‐LOS predicted hospital admission (Crilly et al, ). In terms of hospitalisation, these findings indicate that the nursing care needs of hospitalised patients were higher in comparing to those of the home‐discharged patients.…”
Section: Methodsmentioning
confidence: 99%